CUSTOMER SATISFACTION ON SOCIAL MEDIA: ANALYSING SENTIMENT AND BRAND PERCEPTION THROUGH BIG DATA - Yogi Nurfauzi; Wulandari Wulandari (Adisam Publisher, 2025)
This research aims to analyse the level of customer satisfaction and brand perception on social media through big data-based sentiment analysis methods. By utilising big data technology, data obtained from various social media platforms such as Facebook, Twitter, and Instagram were analysed to identify positive, negative, and neutral sentiments towards brands. This research found a relationship between customer sentiment and brand reputation and loyalty. Positive sentiments contribute to improved customer image and loyalty, while negative sentiments can significantly damage brand reputation. The results demonstrate the importance of continuous monitoring and analysis of social media activity to devise effective marketing and customer service strategies that are responsive to customer needs and perceptions.